2021
DOI: 10.1111/iej.13669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an individualized training course on technical quality and periapical status of teeth treated endodontically by dentists in the Public Dental Service in Norway: An observational intervention study

Abstract: Aim: To investigate the effect of a continuing education course on technical quality and treatment outcome for root filled permanent teeth in Møre and Romsdal County, Norway. Methodology: Fifty-two dentists employed in the Public Dental Service in Møre and Romsdal county, Norway, completed a two-day continuing education course in root canal treatment. Periapical radiographs of root filled teeth treated before and after the course, with at least one-year follow-up were identified and scored for technical qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, a systematic review of root canal retreatment (Ng, Mann, & Gulabivala, 2008), where the majority of included studies had been conducted in hospital and specialist practice settings, found clinical outcomes were not influenced by level of operator experience. Short endodontic technique courses, likely to have been undertaken by many of the General Dental Practitioners, have been reported not to influence PAH outcomes (Jordal et al., 2022; Koch et al., 2015), even though technical aspects of treatment delivery, and TS may be improved (Koch et al., 2015). Given that the Referred cohort PAH outcomes were aligned with those achieved by specialty trainees or specialists (Ng et al., 2011a; Ng, Mann, Rahbaran, et al., 2008), it would suggest that higher level training plays an important role in intra‐operative decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review of root canal retreatment (Ng, Mann, & Gulabivala, 2008), where the majority of included studies had been conducted in hospital and specialist practice settings, found clinical outcomes were not influenced by level of operator experience. Short endodontic technique courses, likely to have been undertaken by many of the General Dental Practitioners, have been reported not to influence PAH outcomes (Jordal et al., 2022; Koch et al., 2015), even though technical aspects of treatment delivery, and TS may be improved (Koch et al., 2015). Given that the Referred cohort PAH outcomes were aligned with those achieved by specialty trainees or specialists (Ng et al., 2011a; Ng, Mann, Rahbaran, et al., 2008), it would suggest that higher level training plays an important role in intra‐operative decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographs taken on admission, on completion of treatment and at control were analysed in the ImageJ program (Schneider et al., 2012). A plug‐in addition (Preus et al., 2015) modified for registrations of endodontic parameters (Jordal et al., 2022) was used for recording radiographic features of interest (see Table S1). The radiographs were anonymized and randomly mixed and the observers were blinded for all clinical data, including the type of irrigation that was used.…”
Section: Methodsmentioning
confidence: 99%
“…From Jordal et al (2022)—‘The project was presented to the Regional Ethics Committee (REC South‐East Norway) without objections (ref no. 2015/265 B) and was approved by the Norwegian Center for Research Data, NSD (Ref no 39991).…”
Section: Process Involved In Developing the Preferred Reporting Items...mentioning
confidence: 99%